Protecting Civil and Political Rights: Comparative Analysis of International Human Rights Mechanisms - Ade Risna Sari; Amtai Alaslan (Eastasouth Institute, 2023)
This research conducts a comparative analysis of international human rights mechanisms to examine their effectiveness in protecting civil and political rights. The research aims to assess the strengths, limitations and contributions of various international mechanisms in protecting these fundamental rights. Part of the study process included a thorough analysis of international human rights treaties, agreements, reports, and case law from regional and international human rights organizations. The focus of the examination is on contrasting the mandates, responsibilities, and management styles of important international human rights institutions, including the Inter-American Commission on Human Rights, the European Court of Human Rights, and the UN Human Rights Council. These international organizations use a variety of tactics and resources to safeguard civil and political rights, which are made evident in its conclusions. The report lists common problems that these systems encounter, such as poor enforcement capacities, disparities in membership and participation, and the potential impact of political interests on decision-making processes. It also looks at how these processes have helped advance civil and political rights all throughout the world. The article discusses significant cases and rulings that have helped establish international and state standards for human rights legislation.